Distribution pattern of surgical affections of the lower urinary tract in dogs: A two-year retrospective study - Adil, Santosh Kumar; Mohindroo, J.; Kumar, Ashwani; Singh, Navdeep; Bansal, N. (Indian Journal of Veterinary Surgery, 2026)
This retrospective study was aimed to study the distribution pattern of surgical affections of the lower urinary tract concerning age, gender, breed, season of occurrence and geographical distribution. Out of a total of 35,494 canine cases presented to the university veterinary hospital, overall occurrence of surgical affections of the lower urinary tract was 0.86%, with the most common condition of urolithiasis and/or concretions in 93.81% dogs followed by urethral prolapse (2.93%), urinary bladder mass (2.28%) and urethral rupture (0.98%). Among urolithiasis cases, Pugs were the most commonly affected breed (27.08%). Urolithiasis was most common in male dogs (79.86%) in the age group of 1-8 yr (77.77%) having a mean age of 4.92±0.14 yr. Most of cases of urolithiasis the belonged to Malwa (southern west) region of the Punjab (66.54%) and witnessed in the winter season (45.49%). All 9 cases of the urethral prolapse were recorded in the male American bully breed, 55.56% of which were juvenile and 66.67% of cases were presented in the rainy season. Bull dog and Bully breeds were the most affected with urinary bladder masses, with no gender predilection. Urethral rupture was seen exclusively in male dogs due to dog bite wounds/trauma.